Prize winning short-horns, how fed and bred - Spencer, Walter H. (My University, 1902)
Introduction: This breed of cattle is better known, more numerous and widely disseminated than any other breed. It originated in the north eastern part of England mainly Durham and Yorkshire, in the valley of river Tees, from which they have been known the world over, as Durhams, and in many localities, in an early day as Teeswater cattle. As early as 1750 the cattle of that region had won a reputation for their large size and good milking qualities, but they were coarse boned and slow in maturing. Some of the early improvers were as follows. Robert and Charles Colling, were connected with the improvement of this breed from 1780-1820, and did more for their improvement, than any other breeder of their time. In 1796, Charles Colling selected and fatted for exhibition a steer that was transported over England, and part of Scotland, in a large wagon as a show. This was the animal known at the “Durham ox,” and when six years old weighed 3024 pounds. Soon after Robert Colling fed a beautiful thoroughbred heifer, and sent her for exhibition through many counties; she was known as the “white heifer that traveled.” Her live weight was 2300 pounds.
Citation: Spencer, Walter H. Prize winning short-horns, how fed and bred. Senior thesis, Kansas State Agricultural College, 1902.
Morse Department of Special Collections
Keywords: Short Horn Cattle; Teeswater Cattle; History; Animal Husbandry; Theses